Automated template matching versus conventional pace-mapping during pvc ablation: results from a randomized controlled trial - Schulz, N; Steven, D; Sultan, A; Van Den Bruck, J H; Woermann, J; Schipper, J; Scheurlen, C; Dittrich, S; Filipovic, D; Erlhoefer, S; Lueker, J (Europace (London, England), 2024)
Abstract Background Pace-mapping has an important role in the ablation of idiopathic premature ventricular contractions (PVC). There is a software with an automated algorithm annotating and visualizing template matching points. Automated template matching (ATM) facilitates the matching process and may thus shorten the procedure duration and potentially increase ablation success. In this randomized study we evaluate whether the use of the automated template matching (ATM) software compared to conventional pace-mapping (PM) influences outcomes and periprocedural parameters in patients undergoing PVC ablation. Methods The study was performed as a prospective randomized controlled single-center clinical trial. Patients scheduled for de-novo PVC ablation were included and randomly assigned to either PVC ablation using the ATM algorithm (ATM) or conventional pace-mapping (PM). The primary endpoint was the procedural outcome represented by the PVC burden after three and twelve months. Secondary endpoints were periprocedural parameters including procedure duration, number, and duration of radiofrequency application (RFA), fluoroscopy (FS) dose, and duration. An interim analysis was predetermined after 72 patients had completed their three-month follow-up. Results After the interim analysis, the study was prematurely ended for futility. At termination of the trial 108 patients had been included. 18 patients dropped out of the study. Out of the remaining 90 patients, 88 patients (97%) have completed the three-month follow-up, and 73 patients (81%) the twelve-month follow-up. The mean age at the time of procedure was 57.3 years [18-82] without significant differences between both groups. Before ablation, the mean PVC burden was 20.8% [0.1-55.0] (ATM: 20.8% [3.0-55.9]; PM: 20.7% [0.1-44.0]; p=0.959). At 3-month follow-up, the mean PVC burden in both groups (ATM: 4.7% [0-29.4]; PM: 3.6% [0-45.7]; p=0.512) showed no significant difference between the groups. At 12-month follow-up the mean PVC burden in both groups (ATM: 3.8% [0-31]; PM: 2.2% [0-25.6]; p=0.282) also resulted in a non-significant difference between the groups. Furthermore, the procedural parameters (table) did not differ significantly between both groups. Conclusion In this randomized trial, the use of the automated template matching software did not result in improved outcomes or procedure-related parameters. Conventional pace-mapping appeared to be equally effective compared to the automated template matching software as used in this study. Table secondary endpoints